NPK fertilization experiments on corn in Minas Gerais state. II. Corn nutrition evaluation by foliar analysis - Santos, Hélio Lopes dos; Filho, Antônio F.C. Bahia; Bahia, Francisco; Magnavaca, Ricardo; Silva, Jairo; Murad, Antônio Miguel; Pacheco, Edson Bolivar (Pesquisa Agropecuaria Brasileira, 2014)
An NFK experiment was installed for three consecutive years in Patos de Minas, Minas Gerais, Brasil, at four different sites, all on a eutrophic “Latossolo roxo”. The experimental design was a 33 factorial, totally confounded as to NPK interactions, group W, and arranged in blocks of nine treatments each. The test crop was corn (Zea mays L.) hybrid Hmd 6999B. Ear leaves were sampled at 50% silk and analyzed for total N, P and K content. Interrelationships between these analysis, and relationships between ear leaf nutrient content, N application, and year were found by multiple regression analysis. Foliar N content and grain production increased linearly throughout the range of N application (0 to 120 kg/ha), eliminating the possibility of establishing a critical N level. Phosphorus content of the ear leaf was strongly influenced by application of N and annual variations in foliar N and P were substantial. Foliar K levels showed little response to applications of N, P, or K.